2011
DOI: 10.1063/1.3584177
|View full text |Cite
|
Sign up to set email alerts
|

Scaled opposite-spin CC2 for ground and excited states with fourth order scaling computational costs

Abstract: An implementation of scaled opposite-spin CC2 (SOS-CC2) for ground and excited state energies is presented that requires only fourth order scaling computational costs. The SOS-CC2 method yields results with an accuracy comparable to the unscaled method. Furthermore the time-determining fifth order scaling steps in the algorithm can be replaced by only fourth order scaling computational costs using a "resolution of the identity" approximation for the electron repulsion integrals and a Laplace transformation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
133
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(133 citation statements)
references
References 35 publications
0
133
0
Order By: Relevance
“…SCS-CIS(D) [58,59] and SOS-CIS(D) [59], SCS-CC2 and SOS-CC2 [60] or SOS-ADC(2) [12,60,61]. A comparison between ADC(2) and SOS-ADC(2) for a subset of the benchmark set employed in this study showed significant differences in the mean errors between ADC(2) and two different versions of SOS-ADC(2) [12].…”
Section: Soppa(scs-mp2) and Soppa(sos-mp2)mentioning
confidence: 87%
“…SCS-CIS(D) [58,59] and SOS-CIS(D) [59], SCS-CC2 and SOS-CC2 [60] or SOS-ADC(2) [12,60,61]. A comparison between ADC(2) and SOS-ADC(2) for a subset of the benchmark set employed in this study showed significant differences in the mean errors between ADC(2) and two different versions of SOS-ADC(2) [12].…”
Section: Soppa(scs-mp2) and Soppa(sos-mp2)mentioning
confidence: 87%
“…It is worth noting that Algorithms I and II could be modified slightly to evaluate scaled opposite-spin CC2 (SOS-CC2). 15 Under the THC approximation, the cost of each SOS-CC2 iteration would be reduced to O(N 3 ) operations. The final contributions to the CC2 energy and singles amplitudes include exchange-like integrals and represent the rate limiting limiting step of the entire THC-CC2 computation.…”
Section: : For All V Domentioning
confidence: 99%
“…12,13 In particular, a) Electronic mail: toddjmartinez@gmail.com CC2 has proven useful in the study of chromophores with extended π -conjugated systems and for excited states with significant charge-transfer character. [14][15][16] In recent years, the density fitting (DF) approximation, also called the resolution of the identity (RI) approximation, has become a popular means of improving the efficiency of many methods in electronic structure theory. [17][18][19][20][21] In particular, DF has been applied to MP2 with great success.…”
Section: Introductionmentioning
confidence: 99%
“…There are highly efficient CC2 and scaled opposite-spin (SOS) CC2 implementations using this approach for excited states. [24][25][26][27][28][29] However, DF reduces only the prefactor, but not the scaling: DF-CC2 still scales as O(N 5 ), the approximate DF-SOS-CC2 method as O(N 4 ).…”
Section: Introductionmentioning
confidence: 99%